2004
DOI: 10.1017/s1014233900001784
|View full text |Cite
|
Sign up to set email alerts
|

Polish Red Cattle breeding: past and present

Abstract: SummaryThe aim of this study was to characterise the Polish Red cattle breed, the only existing native breed in Poland. The origin and conformation of this breed and its historical development, distribution and performance were described. Moreover, the attention was paid to the attempts to improve the breed milk performance by crossbreeding with Jersey, Danish Red and Angler and beef performance by crossbreeding with Black-and-White, Red-and-White, Simmental and beef bulls.Before the Second World War the Polis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…The Polish Red cattle is also characterized by a good adaptation to harsh environmental conditions, which is especially visible in the ability to limit the efficiency (enabling survival of seasonal feed deficiencies), as well as the relatively quick regeneration after condition loss. These features make the cattle of this breed well adapted to mountainous and submountainous living and production conditions (Szarek et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Polish Red cattle is also characterized by a good adaptation to harsh environmental conditions, which is especially visible in the ability to limit the efficiency (enabling survival of seasonal feed deficiencies), as well as the relatively quick regeneration after condition loss. These features make the cattle of this breed well adapted to mountainous and submountainous living and production conditions (Szarek et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Polish Holstein and Polish Red breeds are also characterized by different fat content in milk and different share of muscle and fat tissue, including the presence of intramuscular fat (Szarek et al 2004;Kuczyń ska et al 2012). In our study, large differences in allele frequency were found in the region encompassing some members of FABP (fatty acid-binding protein) genes family (FABP4, 5 and 9).…”
Section: Discussionmentioning
confidence: 53%
“…The Polish Holstein and Polish Red breeds are also characterized by different fat content in milk and different share of muscle and fat tissue, including the presence of intramuscular fat (Szarek et al . ; Kuczyńska et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations